Generative repair: everyday infrastructuring between DIY citizen initiatives and institutional arrangements. Issue 4 (2nd October 2022) - Hector, Philip; Botero, Andrea
ABSTRACT: DIY citizen initiatives exploring everyday-life practices such as collective making or repair are on the rise. These are characterised by the resources, local knowledge, and volunteer labour they mobilise but also by fragility of long-term sustainment. To understand what is at stake in sustaining them, the authors conducted a case study of a longstanding DIY citizen initiative in Berlin, cross-checking the findings by interviewing employees of two supporting institutional arrangements and organisers of three further DIY initiatives nearby. The study revealed how the DIY initiatives tie together roles and resources to provide concrete everyday infrastructure for citizens while dependent on resources such as space, insurance, legitimacy, and knowledge to navigate surrounding bureaucracy, provided largely via various institutional arrangements. Conversely, these established institutional arrangements benefit from DIY initiatives' local knowledge, authenticity, and expertise. Finally, both sides wish to gain fuller mutual understanding and dialogue-related competencies. The findings highlight the generative repair, performed by both citizen initiatives and the institutional arrangements, that makes their change agendas relevant and lasting. They also point to potential value from considering some of these attempts as forms of infrastructuring with relevance for contemporary participatory design practices.